Aproveitamento da biomassa remanescente da colheira de cana-de-açucar para cogeração - Blanco, Karla Meneguetti (2013)
In this work was studied the use of sugar cane straw, material remnant of mechanical harvesting from sugar cane without burning, as solid fuel in boilers. The use of biomass is required, it presents itself as an alternative raw material with energetic potential interesting. The straw is used as fuel, complementing the role of the crushed sugar cane, currently used, thus increasing the energy efficiency of the process. The calorific value of this material, around 4000 kcal kg-1, is equivalent to sugar cane bagasse, which makes it no longer a disposable material, but an important product to add value in the biofuels industry. Numerous studies point to the relationship 1 ton of trash corresponds energetically 1.2 to 2.5 barrels of American petroleum, depending on the humidity and the mass and that in 1 ha of sugar cane obtained from 4 to 10 tons of trash to approximate moisture 15-20%. However, the sector still faces difficulties in establishing a viable technology in the gathering of this coproduct from the field to its destination industry. Even in the face of this obstacle, promising studies ensure that this technology will soon be dominated. The results of this study, the mean values obtained for the calorific value of straw varieties were RB835054 and RB867515 of 4100 kcal kg-1 and 4300 kcal kg-1 (dry basis), respectively. The proportion corresponding to fractions green leaf, dry leaf and leaf pointer in relation to total plant resulted in an average of 20%, which meets the material available for use. Besides that, the estimated yield for the trash was on average 16 tons per hectare for each variety. The results demonstrate that the proposed methodology has met the requirements expected of obtaining data that allow a decision. But we still need to seek technical, economic and environmental viability of using straw as another by product of considerable agricultural market insertion